Economic effects of simplified procedures for claiming cross-border tax reliefs - Serena Fatica; Jonathan Pycroft; Andrzej Leszek Stasio; Daniel Stoehlker (European Commission, Joint Research Centre (JRC), 2023)
We examine the effect of compliance frictions in reclaiming foreign withholding taxes on Foreign Portfolio Investments (FPI) using a comprehensive panel of FPI stocks of 83 countries, including EU Member States, between 2005 and 2019 and country-pair-specific withholding tax rates. We find a negative and statistically significant elasticity of the FPI stock of equity and debt holdings to non-refundable withholding taxes. The estimated elasticities imply that a 10 percentage point reduction in non-refundable withholding taxes increases the FPI stock of equity holdings by 8.2%. In a second step, we employ a general equilibrium model to quantify the macroeconomic implications of compliance frictions. In absence of costs in the withholding tax reclaim process, average GDP in the EU27 countries would increase by 0.10%, capital and wages would rise by 0.21% and 0.06%, respectively, suggesting noticeable macroeconomic costs arising from such compliance frictions.
Keywords: 330